2017
DOI: 10.3102/0034654317704307
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mobile-Computer-Supported Collaborative Learning: Meta-Analysis and Critical Synthesis

Abstract: One of the trends in collaborative learning is using mobile devices for supporting the process and products of collaboration, which has been forming the field of mobile-computer-supported collaborative learning (mCSCL). Although mobile devices have become valuable collaborative learning tools, evaluative evidence for their substantial contributions to collaborative learning is still scarce. The present meta-analysis, which included 48 peer-reviewed journal articles and doctoral dissertations written over a 16-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
4
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 118 publications
(187 reference statements)
5
76
4
9
Order By: Relevance
“…In addition, the learners were frequently situated in learning contexts across multiple real‐world locations (eg, a museum, science park or garden) rather than in the classroom only. This result is different from the review reported by Sung et al (), who stated that researchers frequently conducted mobile language learning in classrooms. It is inferred that these changes might be due to the increasing diversity of the application domains; and hence, the criteria for researchers to design mobile learning activities changed as well.…”
Section: Discussioncontrasting
confidence: 96%
“…In addition, the learners were frequently situated in learning contexts across multiple real‐world locations (eg, a museum, science park or garden) rather than in the classroom only. This result is different from the review reported by Sung et al (), who stated that researchers frequently conducted mobile language learning in classrooms. It is inferred that these changes might be due to the increasing diversity of the application domains; and hence, the criteria for researchers to design mobile learning activities changed as well.…”
Section: Discussioncontrasting
confidence: 96%
“…The main reasons lie in two aspects. On the one hand, it was impossible for learners to get familiar with the mobile devices, software, and tasks within a very short time slot (Sung et al, 2017). On the other hand, the effects of long intervention duration might decrease because of a loss of novelty sense for mobile devices (Cheung and Slavin, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2.3 Teachers' increased knowledge of problematic mobile phone use Sung et al (2017) have discussed how vague rules and division of labor could cause problems in students' school activities with mobile phones. To overcome such problems, students' off-task behavior should be reduced through a division of labor, increasing teacher control.…”
Section: Teachers' Increased Knowledge Of Supportive Mobile Phone Usementioning
confidence: 99%
“…Moreover, the theory has been previously used to understand how conflicts between people can change (Engeström 1987(Engeström , 2004Engeström et al 2005) and is a well-established theory that has long proven it usefulness. It has been acknowledged for the opportunity it provides to understand activities that implement mobile phones (Chung et al 2019;Sung et al 2017;Zurita and Nussbaum 2007). CHAT is a dialectical approach, meaning that processes and transformations are key issues.…”
Section: Theoretical Stancementioning
confidence: 99%
See 1 more Smart Citation